Students' Perceptions of the Causes of Low Performance in Principles of Accounting: A Case Study at Kolej Poly-Tech MARA, Bangi - Nor Affidah, Yahaya (2010)
This study has been carried out among the students in the business administration diploma programme at Kolej Poy-Tech Mara, Bangi. The objective of this study is to determine what they consider to be the major obstacles to successfully completing the required course in Principles of Accounting. It is generally agreed that the students' performance in this course is unacceptably low. For the purpose of this study, two research issues have been developed; what are the obstacles to the students' which are thought to be the causes of low performance in the Principles of Accounting course, and can all the obstacles listed by students be categorized as core and supplemented obstacles. To achieve the objective and also to answer the research issues, this dissertation employs a quantitative method i.e. - survey research. The students were offered 28 potential obstacles which might contribute to their low achievements plus one open-ended question. The study showed that the significant obstacles were the teaching technique, advising and general obstacles. This finding can hopefully be used to help the management and lecturers to understand the causes of variations in students' performance as it would assist them in developing appropriate teaching strategies conducive to the learning needs of their students. A comparison of the findings of this study and those of previous research is also discussed.